Like a bridge over troubled water : an ethnography on strategies of bodily navigation of male refugees in Cape Town - Junck, Leah Davina (Mankon, Bamenda : Langaa Research & Publishing CIG, 2018)
In spite of South Africa's progressive constitution, citizen's intolerance of non-citizens, refugees and economic migrants has escalated in recent years. What is more, xenophobic attacks are covered in the public discourse as mere episodes of crisis and often rather fuel rhetoric of national machismo than leading to an acknowledgement of the stories and experiences of people seeking refuge and being exposed to hostility on an everyday basis. This ethnography engages with the strategies employed by a group of refugee men from different African countries in surviving and stabilising their existence in the 'mother city' Cape Town in the face of precarity. It grapples with questions of how the men manage to bring about certainty in the face of unpredictability and extends its focus to the men's dreams and the modes by which these are sought to be achieved. It thereby highlights the ways in which objectifications as refugees and less-than-human are somewhat transcended by navigating spaces with care, purpose and imagination.
Male refugees in Cape Town -- Troubling bodies and the mother city -- The challenged, corporeal body -- Researching 'disposable bodies' -- Bodies taking shape : on corporeal resistance to societal exclusion -- Dream until your dreams come true? On bodily mappings of self -- Conclusion.
Includes bibliographical references (pages 77-82).
Online resource; title from digital title page (viewed on August 27, 2018).
JSTOR
Keywords: Refugees -- South Africa -- Cape Town -- Social conditions; Refugees -- Abuse of -- South Africa -- Cape Town; Xenophobia -- South Africa -- Cape Town; Machismo -- South Africa -- Cape Town; Immigrants -- South Africa -- Cape Town -- Social conditions; Electronic books; Réfugiés -- Afrique du Sud -- Le Cap -- Conditions sociales; Réfugiés -- Violence envers -- Afrique du Sud -- Le Cap; Xénophobie -- Afrique du Sud -- Le Cap; Machisme -- Afrique du Sud -- Le Cap; Livres numériques.; e-books.; SOCIAL SCIENCE -- Emigration & Immigration; SOCIAL SCIENCE -- Ethnic Studies -- General; Immigrants -- Social conditions; Machismo; Refugees -- Abuse of; Refugees -- Social conditions; Xenophobia; South Africa -- Cape Town